A Statistical Model of the Gross Analysis of Transaction Flows - Savage, I. Richard; Deutsch, Karl W. (Econometrica, 1960)
This is applicable to the flow of any kind of quantifiable transactions, and to matrices from three to more than one hundred actors, utilizing a 650 IBM electronic computer or similar equipment. The method develops a matrix of expected or baseline data from assumptions of complete indifference among the actors, and measures the plus or minus differences between this baseline value and the actual amount of transactions in each direction for every pair of actors. It thus removes gross size effects and permits tentative inferences about the distribution of preferences among pairs of larger groups of actors; about degrees of clustering or integration among actors; and about changes over time, if several matrices are used. It thus locates interesting pairs or groups for further study. Import-export data are used as an example to show the detailed application of the method. For a given year and a group of countries, the importexport data can be arranged like a contingency table, except the diagonal cells are zero and the other entries are quantities of money, a continuous variable instead of a discrete variable. A describing the data and techniques for the statistical analysis are presented. This is a null model in the sense that the departures from it are of primary interest. The North Atlantic Area (1928) is used as an illustration.